Mass Spectrometry-Based Network Analysis Reveals New Insights Into the Chemodiversity of 28 Species in Aspergillus section Flavi - Wang, Xinhui; Subko, Karolina; Kildgaard, Sara; Frisvad, Jens C.; Larsen, Thomas O. (Frontiers in Fungal Biology, 2021)
Aspergillus section Flavi includes some of the most famous mycotoxin producing filamentous fungi known to mankind. In recent years a number of new species have been included in section Flavi, however these species have been much less studied from a chemical point of view. In this study, we explored one representative strain of a total of 28 fungal species in section Flavi by systematically evaluating the relationship between taxonomy and secondary metabolites with LC-MS/MS analysis for the first time and dereplication through an in-house database and the Global Natural Product Social Molecular Networking (GNPS) platform. This approach allowed rapid identification of two new cyclopiazonic acid producers (A. alliaceus and A. arachidicola) and two new tenuazonic acid producers (A. arachidicola and A. leporis). Moreover, for the first time we report species from section Flavi to produce fumifungins and sphingofungins B-D. Altogether, this study emphasizes that the chemical diversity of species in genus Aspergillus section Flavi is larger than previously recognized, and especially that understudied species are prolific producers of important mycotoxins such as fumi- and sphingofungins not previously reported from this section. Furthermore, our work demonstrates Global Natural Product Social (GNPS) Molecular Networking as a powerful tool for large-scale chemotaxonomic analysis of closely related species in filamentous fungi.